2011
DOI: 10.1098/rsbl.2011.0916
|View full text |Cite
|
Sign up to set email alerts
|

Metapopulation models for seasonally migratory animals

Abstract: Metapopulation models are widely used to study species that occupy patchily distributed habitat, but are rarely applied to migratory species, because of the difficulty of identifying demographically independent subpopulations. Here, we extend metapopulation theory to describe the directed seasonal movement of migratory populations between two sets of habitat patches, breeding and non-breeding, with potentially different colonization and extinction rates between patch types. By extending the classic metapopulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 20 publications
0
48
0
Order By: Relevance
“…A recent review identified over 60 metrics (Rayfield et al, 2010), which could be classified into four categories: Monarch butterflies (Flockhart et al, 2015) Chinook salmon Oncorhynchus tshawytscha (Greene and Beechie, 2004) Maintain a minimum of 1000 pairs of Kirtland's warbler Setophaga kirtlandii (Byelich et al, 1985) Northern pintail Anas acuta (Mattsson et al, 2012) Cerulean warbler Dendroica cerulea conservation plan (Cerulean Warbler Technical Group, 2007) Bridled nailtail wallabies Onychogalea fraenata (Rout et al, 2009) Modeled per-capita contributions for metapopulations (Runge et al, 2006 (Culver et al, 2009) Levins metapopulation model adapted to migratory populations (Taylor and Hall, 2012) Contribution to colonization for Glanville fritillary butterfly Melitaea cinxia (Ovaskainen and Hanski, 2003) Giant pandas Ailuropoda melanoleuca (Xu et al, 2006) Maximize number of occupied habitats Tennessee purple coneflower Echinacea tennesseensis (Bowen, 2011) Mexican spotted owls Strix occcidentalis lucida (Urban and Keitt, 2001) *Indicates that additional information linking the population to another unknown is required (i.e., for climate change, information on the impact of climate scenarios on population parameters is required; for ecosystem services, a relationship linking the provision of the service to population size is required).…”
Section: Graph-based Metricsmentioning
confidence: 99%
“…A recent review identified over 60 metrics (Rayfield et al, 2010), which could be classified into four categories: Monarch butterflies (Flockhart et al, 2015) Chinook salmon Oncorhynchus tshawytscha (Greene and Beechie, 2004) Maintain a minimum of 1000 pairs of Kirtland's warbler Setophaga kirtlandii (Byelich et al, 1985) Northern pintail Anas acuta (Mattsson et al, 2012) Cerulean warbler Dendroica cerulea conservation plan (Cerulean Warbler Technical Group, 2007) Bridled nailtail wallabies Onychogalea fraenata (Rout et al, 2009) Modeled per-capita contributions for metapopulations (Runge et al, 2006 (Culver et al, 2009) Levins metapopulation model adapted to migratory populations (Taylor and Hall, 2012) Contribution to colonization for Glanville fritillary butterfly Melitaea cinxia (Ovaskainen and Hanski, 2003) Giant pandas Ailuropoda melanoleuca (Xu et al, 2006) Maximize number of occupied habitats Tennessee purple coneflower Echinacea tennesseensis (Bowen, 2011) Mexican spotted owls Strix occcidentalis lucida (Urban and Keitt, 2001) *Indicates that additional information linking the population to another unknown is required (i.e., for climate change, information on the impact of climate scenarios on population parameters is required; for ecosystem services, a relationship linking the provision of the service to population size is required).…”
Section: Graph-based Metricsmentioning
confidence: 99%
“…Various mathematical models have been developed to help broaden understanding of the role of the migration process and how it may be affected by the aforementioned environmental changes (Taylor and Hall, 2012;Jonzén et al, 2007;Sutherland, 1996). These models generally do not consider the annual cycle in its entirety, implicitly ruling out the possibility of seasonal interactions influencing survival predictions.…”
Section: Introductionmentioning
confidence: 99%
“…2). Assuming that migratory connectivity takes place as sequential events (see Taylor & Hall 2011), the nearest neighbor N j can be described as a multiple of N i , i.e. as a ratio of seasonal differences in abundance at patch i, given that migration in either direction is proportional to patch abundance:…”
Section: Incidence Function Modelmentioning
confidence: 99%
“…As a further aspect of life-history traits, the role of dispersal capabilities of sub-populations and as a corollary, connectivity, between occupied habitats has only begun to be understood in practice (see Fagan et al 2001, Metcalfe 2006. Connectivity is an important parameter to explain persistence of meta-populations within migratory networks (Taylor & Hall 2011) and thus changes in local abundance (Simpfendorfer et al 2002). As a prerequisite to connectivity between patches, habitat quality within patches must be sufficient to maintain sub-populations (Hodgson et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation